Legal interpretation and justice (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In the practice of juridical hermeneutics, justice becomes a comprehensive key ofpractical, intersubjective and experimental nature. This way, law and justice interactfrom a point of view which differs from the jusnaturalism rational and methaphisicidentity or the distinctness defined by legal positivism. The analysis focused on theoperability of the concept of justice as concept of the sense of justice in juridicalhermeneutics splits this dimension of the applicative justice from other conceptsmore focused in the concept of politics -mainly distributive- or the moral virtues.The application of the justice to the legal dispute -as juridical hermeneutics ambition-will follow the path starting from the judgement as part of an interpreting procedurewhere reflexive and discursive discerning as wit of the person cooperate, andending with praxis horizons.
Keywords: Key words; justice; application; sense of justice; hermeneutics; juridical hermeneutics; judgement; comprehension-interpretation; dispute; practice; praxis.